Adipose tissue protects against skin photodamage through CD151- and AdipoQ- EVs - Yan-Wen Wang; Poh-Ching Tan; Qing-Feng Li; Xue-Wen Xu; Shuang-Bai Zhou (Cell Communication and Signaling)
Abstract To clarify the protective effects of subcutaneous adipose tissue (SAT) against photodamage, we utilized nude mouse skin with or without SAT. Skin and fibroblasts were treated with adipose tissue-derived extracellular vesicles (AT-EVs) or extracellular vesicles derived from adipose-derived stem cells (ADSC-EVs) to demonstrate that SAT protects the overlying skin from photodamage primarily through AT-EVs. Surprisingly, AT-EVs stimulated fibroblast proliferation more rapidly than ADSC-EVs did. The yield of AT-EVs from the same volume of AT was 200 times greater than that of ADSC-EVs. To compare the differences between AT-EVs and ADSC-EVs, we used a proximity barcoding assay (PBA) to analyze the surface proteins on individual particles of these two types of EVs. PBA analysis revealed that AT-EVs contain diverse subpopulations, with 83.42% expressing CD151, compared to only 1.98% of ADSC-EVs. Furthermore, AT-EVs are internalized more rapidly by cells than ADSC-EVs, as our study demonstrated that CD151-positive AT-EVs were endocytosed more quickly than their CD151-negative counterparts. Additionally, adiponectin in AT-EVs activated the AMPK pathway and inhibited the NF-κB pathway, enhancing fibroblast protection against photodamage. The significantly higher yield and faster acquisition of AT-EVs compared to ADSC-EVs underscore their potential for broader applications. Graphical Abstract AT mitigates skin photoaging via AT-EVs, which consist of 14 subpopulations and express more CD151 and APN on their surface, as determined by PBA sequencing. CD151 facilitates faster cellular recognition and uptake of AT-EVs. APN activates AdipoR to stimulate the AMPK pathway and inhibit the NF-κB pathway, reducing ROS and DNA damage in fibroblasts. This results in improved skin histology, increased collagen production, a reduction in senescent cells, and decreased ROS accumulation. (Created with BioRender.com)